Prevalence of risk factors for cardiovascular and kidney disease in Brazilian healthy preschool children - da Silva, Adriana Cândida (World J Nephrol, 2016)
AIM: To investigate the prevalence of nutritional parameters of risk for cardiovascular disease (CVD) and kidney diseases in healthy preschool children. METHODS: This is an observational cross-sectional study with 60 healthy children, of both genders, aged two to six years old and 56 mothers, in Belo Horizonte, Minas Gerais, Brazil. Preschool children and their families with regular activities at public schools were invited to paticipate in the study. The following characteristics were assessed: Socio-demographic condictions, clinical health, anthropometric, biochemical, lifestyle and data on food consumption. The 56 healthy children were divided into two groups, overweight (C1) and non-overweight (C2), as well as their mothers, respectively, in overweight (M1) and non-overweight (M2). Nutritional status was defined according to results obtained through the Anthro(®) Software for nutritional analysis. RESULTS: Thirty-five children were male, with mean age of 4.44 ± 1.0 years old. Eighty-nine percent of them were eutrophic, 86.7% were sedentary and they had five meals a day. Body mass index (BMI) for age and total cholesterol (TC) was higher on C1 (P = 0.0001) and high density lipoprotein cholesterol (HDL-c) was higher on C2. Mothers were 32.5 ± 7.1 years old, mostly married and employed. Eighty-six percent of them were sedentary and 62.5% were overweight with BMI = 26.38 ± 5.07 kg/m(2). Eighteen percent of the overweight mothers had isolated total hypercholesterolemia (TC levels elevated) and 12.5% had low HDL-c levels. The present study showed an association between overweight and obesity during the preschool years and the correspondent mothers’ nutritional status of overweight and obesity (OR = 4.96; 95%CI: 0.558-44.17). There was a positive correlation between the food risk associated with CVD by children and mothers when their consumption was 4 times/wk (P = 0.049; r = 0.516) or daily (P = 0.000008; r = 0.892). CONCLUSION: Analyzed children showed high rates of physical inactivity, high serum cholesterol levels and high consumption of food associated with risk for CVD and renal disease. Changes in habits should be encouraged early in kindergarten.